2018
DOI: 10.1021/acs.chemmater.8b00163
|View full text |Cite
|
Sign up to set email alerts
|

Origin of High Capacity and Poor Cycling Stability of Li-Rich Layered Oxides: A Long-Duration in Situ Synchrotron Powder Diffraction Study

Abstract: High-energy Li1.17Ni0.19Co0.10Mn0.54O2 (HE-NCM) is a lithium-rich layered oxide with alternating Li- and transition-metal (TM) layers in which excess lithium ions replace transition metals in the host structure. HE-NCM offers a capacity roughly 50 mAh g–1 higher compared to that of conventional layered oxides but suffers from capacity loss and voltage fade upon cycling. Differential capacity plots (taken over 100 cycles) show that the origin of the fading phenomenon is a bulk issue rather than a surface degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
151
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 41 publications
4
151
1
Order By: Relevance
“…We have highlighted several mechanisms that appear to be consistent with available data (illustrated in Figure 4): the oxidation of Mn 4+ to Mn 7+ accompanied by a migration from octahedral to tetrahedral sites; the formation of peroxide ions or trapped molecular oxygen; and the formation of Mn 7+ followed by the spontaneous dimerization of oxygen. We have explored in depth the oxidation of Mn 4+ to Mn 7+ and found this hypothesis to be compatible with experimental and firstprinciples thermodynamics, supported by the observation of tetrahedral occupancy at the end of charge through XRD, 93 and consistent with the electrochemical behavior in Cr-based cathode materials which are known to undergo tetrahedral/octahedral migration. [85][86][87][88] The anomalous capacity may, however, involve contributions from multiple redox mechanisms.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…We have highlighted several mechanisms that appear to be consistent with available data (illustrated in Figure 4): the oxidation of Mn 4+ to Mn 7+ accompanied by a migration from octahedral to tetrahedral sites; the formation of peroxide ions or trapped molecular oxygen; and the formation of Mn 7+ followed by the spontaneous dimerization of oxygen. We have explored in depth the oxidation of Mn 4+ to Mn 7+ and found this hypothesis to be compatible with experimental and firstprinciples thermodynamics, supported by the observation of tetrahedral occupancy at the end of charge through XRD, 93 and consistent with the electrochemical behavior in Cr-based cathode materials which are known to undergo tetrahedral/octahedral migration. [85][86][87][88] The anomalous capacity may, however, involve contributions from multiple redox mechanisms.…”
Section: Resultssupporting
confidence: 66%
“…11,26,28,30 Second, a recent in-situ diffraction study on a Li-excess cathode concluded that transition-metal ions migrate to tetrahedral sites in the Li layer during charge and return to octahedral sites on discharge. 93 Lastly, the Raman feature attributed to the reversible formation of peroxide ions is also consistent with tetrahedral Mn 7+ . 45,94 Figure 4(a) and (b) illustrates the two alternatives to the lattice oxygen redox hypothesis that we have explored so far.…”
Section: Critical Analysis Of Mn Oxidationmentioning
confidence: 61%
“…Therefore, the oxygen release is a side reaction occurring at the HE-NCM nearsurface region, 25 while reversible and irreversible transition metal migration in the bulk material cause the main voltage fading and the high hysteresis. 35,45,46 Figure 5 depicts the dQ/dV plots for cycle 3, cycle 20, and cycle 48 extracted from the cycling data shown in Figure 4. Hereby, cycle 3 is the first C/5 cycle between 2.0 V and 4.7 V and therefore is subjected to the same cycling conditions as cycle 20 and 48.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33][34] Therefore, it is suggested that high degrees of delithiation and reversible oxygen redox trigger reversible and irreversible transition metal migration within the bulk material, leading to voltage fading and to the large charge/discharge voltage hysteresis due to the hindered lithium diffusion within the bulk material. 14,[35][36][37][38] In contradiction to the hypothesis of bulk oxygen release and bulk structural transformation, recent studies give clear evidence that the bulk structure is preserved, while a relatively small fraction of transition metals (about 10% over 100 cycles) 35 migrate reversibly and over extended charge/discharge cycling irreversibly between the transition metal and the lithium layers, leading to changes of the bulk material thermodynamics like the charge and discharge potentials as well as to the observed voltage fading. 25,35 In this study, we will examine the effect of oxygen release onto the bulk and the surface structure of HE-NCM and correlate it with the macroscopic electrochemical performance of the material.…”
mentioning
confidence: 96%
See 1 more Smart Citation